PENGEMBANGAN KETERAMPILAN BERFIKIR KRITIS SISWA MELALUI PEMBELAJARAN IPS MI - Nurlaili Dina Hafni (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2020)
This research works for two reasons; first, academically, variative method will be highly effective and efficient in teaching quality. Meanwhile if this does not develop well, it is an obstacle for the achievement of learning objectives, the achievement of critical thinking skills. Second, based on the first observation, it was found that there are some social studies teacher who teach the student by speech method, asking-answer question, and giving works. It will not develop student critical thinking based on what FRISCO stated. The research purpose is to identify and analyze the learning method of social studies teacher in MIN Rejoso to developing student critical thinking skills. It is field research with qualitative approach. The data is collected by interview, observation, and document analysis. The data analysing technicque uses “discourses analysis”. The research found is the method used by social studies teacher in MIN Rejoso Peterongan Jombang can not develop the student critical thinking skills. The causes is there are some teacher‟s view that social studies is similar with rote and stories. The paradigm that may admit the teacher is everything, teachers is lazy to design critical learning due to lot of other works that must finished, and limited facilities.